2020
DOI: 10.21203/rs.3.rs-40112/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Community Psycho-behavioral Responses during the outbreak of novel coronavirus (2019-nCoV): A cross-sectional study

Abstract: Abstract Objectives: To examine the public’s knowledge and psychological impact during the outbreak of (2019-nCoV) and the extent to which precautionary measures have been adopted. We conducted an online survey on precautionary measures against (2019-nCoV), self-health evaluation, knowledge about (2019-nCoV), and appraisal of crisis management. The psychological impact was assessed by the General Anxiety Disorder 7-item scale. Results:<… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This finding was similar to one of the large Chinese surveys, which reported 35% of the respondents' experienced psychological distress during this pandemic ( 7 ). On the contrary, a recent online survey from Malaysia reported 72.1% moderate to severe anxiety ( 26 ), while a study from Egypt found 82% mild to moderate anxiety symptoms during this pandemic ( 27 ). The difference observed among different countries regarding psychological well-being could be explained by different healthcare infrastructures, the variability in responsiveness of the health system, and the prevention and control measures taken against the pandemic.…”
Section: Discussionmentioning
confidence: 93%
“…This finding was similar to one of the large Chinese surveys, which reported 35% of the respondents' experienced psychological distress during this pandemic ( 7 ). On the contrary, a recent online survey from Malaysia reported 72.1% moderate to severe anxiety ( 26 ), while a study from Egypt found 82% mild to moderate anxiety symptoms during this pandemic ( 27 ). The difference observed among different countries regarding psychological well-being could be explained by different healthcare infrastructures, the variability in responsiveness of the health system, and the prevention and control measures taken against the pandemic.…”
Section: Discussionmentioning
confidence: 93%
“…Telecommuting is an effective measure for preventing COVD-19 infection, and it may have had a positive effect on reducing job stress such as anxiety and depression. 33 34 We speculate that the elimination of infection anxiety related to COVID-19 has influenced the reduction in work stress.…”
Section: Discussionmentioning
confidence: 98%
“…There was no significant trend for commuting distance, although there was a significant trend for commuting time, and the relationship between commuting time and general infection anxiety became stronger as commuting time increased. Several studies have reported that anxiety causes people to apply infection prevention measures [18, 19]. The use of public transportation, commuting time, and commuting distance are all associated with anxiety about infection due to commuting; the longer the commuting time and distance, the more likely are people to voluntarily intensify infection prevention measures.…”
Section: Discussionmentioning
confidence: 99%